Menginisiasi Kerja Sama Riset Internasional yang Setara, Adil, dan Bermanfaat bagi Indonesia - Nugroho, Agustinus Hadi (Journal of Politics and Democracy, 2021)
International research collaboration can be understood as a social process within the realm of research, as it embodies a dialectical interplay between the interests of Indonesia and those of foreign partners. As a social process, international research collaboration should thus be analyzed through the theoretical lens of dialectical materialism. Within this framework, it is essential to distinguish between the infrastructural (base) and superstructural (superstructure) aspects. The infrastructural aspect of international research collaboration lies in its financial dimension, while the superstructural aspects encompass institutional and knowledge-related dimensions. Optimizing the benefits of international research collaboration requires more than merely proposing practical policy measures; it also demands an understanding of the preconditions that shape the ecosystem of such collaboration. These preconditions particularly concern latent inequalities that often go unnoticed in the relationships between local and foreign partners. By recognizing and addressing these underlying asymmetries, the government can better formulate policy strategies grounded in principles of equity, thereby fostering international research collaborations that serve Indonesia’s national interests more effectively and sustainably.